A Conceptual Model of Hibah Giving Behavior - Said, Nadzirah Mohd; Saad, Ram Al Jaffri (International Review of Management and Marketing, 2016)
The frozen estate in Malaysia is increasing year to year. Many researchers suggest that giving hibah as one of the solution to reduce the number of frozen estate in Malaysia. Nevertheless, the previous researches indicate that the hibah giving behavior among Muslim in Malaysia is still low. It raises the question of what are the factors that will influence someone to give hibah. Therefore, the purpose of this paper is to propose model of hibah giving behavior. The proposed model was introduced to examine whether attitude, religious value and service quality are the determinants of hibah giving behavior. The review of past literatures conceptualized that attitude and religious value as the internal factors while service quality as the external factor that can influence the hibah giving behavior. Three hypotheses were proposed to see the relationship between variables and hibah giving behavior. Lastly, both theoretical and practical implications were also discussed in this study. Keywords: Hibah Giving Behavior, Attitude, Service Quality, Religious Value. JEL Classifications: D1, D31, M49, Z12